Implementasi Problem Based Learning pada Mata Pelajaran PPKn (Studi Kasus Implementasi Kurikulum 2013 di Kelas XI SMK Muhammadiyah 4 Surakarta Tahun Pelajaran 2014/2015) - ZULAIHA, Ellida Nur, Drs. Achmad Muthali'in, M.Si (2015)
Curriculum development has a lot of influence among the learning model. Another difference in the learning model. Many kinds of learning models with different implementation measures, but has the same objective, namely the achievement of students' understanding. The learning model is the support of the learning process in achieving its objectives. The purpose of this study was to describe the implementation, constraints, and solution of problems Problem Based Learning on the subjects PPKn in SMK Muhammadiyah 4 Surakarta. This study is a qualitative research, with data collection through interviews, observation, documentation. The validity of the data using triangulation sources and data collection techniques. Data analysis was performed with an interactive model that includes data collection, data reduction, data presentation, and conclusion. PBL implementation on the subjects PPKn in SMK Muhammadiyah Surakarta 4 of them should run in accordance with the student activity (active thinking, communicating, searching and processing data and concluded), data collection, formulation answer the problem, and the completion of the formulation of the problem. The PBL implementation procedurally running well without any missed steps, but in terms of the process there are some obstacles. Constraints faced were less active students, the lack of participation of students, the lack of cooperation of students, and solving the problems within one point of view only. Solutions to overcome these obstacles is to optimize the role of the teacher as a facilitator, encouraging students to be active and participative as well as adding resources required reading for students.